Cellular Ca2+ Signals Generate Defined pH Signatures in Plants - Behera, Smrutisanjita; Zhaolong, Xu; Luoni, Laura; Bonza, Maria Cristina; Doccula, Fabrizio Gandolfo; De Michelis, Maria Ida; Morris, Richard J.; Schwarzländer, Markus; Costa, Alex (The Plant cell, 2018)
Ca2+ play a key role in cell signaling across organisms. The question of how a simple ion can mediate specific outcomes has spurred research into the role of Ca2+ signatures and their encoding and decoding machinery. Such studies have frequently focused on Ca2+ alone and our understanding of how Ca2+ signaling is integrated with other responses is poor. Using in vivo imaging with different genetically encoded fluorescent sensors in Arabidopsis (Arabidopsis thaliana) cells, we show that Ca2+ transients do not occur in isolation but are accompanied by pH changes in the cytosol. We estimate the degree of cytosolic acidification at up to 0.25 pH units in response to external ATP in seedling root tips. We validated this pH-Ca2+ link for distinct stimuli. Our data suggest that the association with pH may be a general feature of Ca2+ transients that depends on the transient characteristics and the intracellular compartment. These findings suggest a fundamental link between Ca2+ and pH dynamics in plant cells, generalizing previous observations of their association in growing pollen tubes and root hairs. Ca2+ signatures act in concert with pH signatures, possibly providing an additional layer of cellular signal transduction to tailor signal specificity.